Three inhibitory phenolic acids against common ragweed (Ambrosia artemisiifolia L.) had a minimal effect on maize growth in vitro and in vivo. - Laura Pismarović; Valentina Šoštarčić; Kristina Kljak; Boris Lazarević; Maja Šćepanović (PLoS ONE)
With the increasing demand for non-chemical weed control methods, phenolic acids have shown promise due to their natural weed inhibitory potential. In this study, the inhibitory effect of ferulic acid, vanillic acid and p-coumaric acid was investigated on Ambrosia artemisiifolia L. and the selectivity of Zea mays L. against these phenolic acids was tested. The seeds of A. artemisiifolia and Z. mays were treated in vitro with three phenolic acids at doses of 200-600 × 10-7 mol and in vivo foliar on A. artemisiifolia and Z. mays plants. While all phenolic acids had effects on the early growth of A. artemisiifolia, p-coumaric acid significantly reduced the length of radicle and hypocotyl by more than 60% while the effects on Z. mays were minimal. In vivo assessments using chlorophyll fluorescence and multispectral imaging showed selective stress responses in A. artemisiifolia but not in Z. mays after foliar application. The in vitro results show that p-coumaric acid is a promising compound for the control of A. artemisiifolia. However, these phenolic acids at these doses led to an insufficient reduction in photochemical efficiency. Therefore, these natural compounds need to be combined with other methods of weed control.